Victoria Debates Its Post-industrial Reality: Tourism, Deindustrialization, and Store-Hour Regulations, 1900-1958 - Dawson, Michael (Urban History Review / Revue d'histoire urbaine, 2007)
By examining local debates about store-hour regulations in Victoria, BC, this article highlights the extent to which the city's decision to pursue tourism promotion as an economic alternative to traditional industry divided the local community. Some community members championed tourism as an effective alternative economic strategy and fought to eliminate the city's store-hour restrictions, especially the Wednesday half-holiday, because they believed these restrictions limited tourist expenditures. Others strenuously opposed the elimination of these restrictions on the grounds that they served the social and cultural interests of the local community. The article calls for a more flexible understanding of “deindustrialization” that views the term less as an “era” and more as an inherent characteristic of capitalism and argues that the recent literature on deindustrialization holds important lessons for historians examining the period before 1970.